The MAVERIC Survey: A Transitional Millisecond Pulsar Candidate in Terzan 5 - Bahramian, A.; Strader, J.; Chomiuk, L.; Heinke, C.; Miller-Jones, James; Degenaar, N.; Tetarenko, A.; Tudor, V.; Tremou, E.; Shishkovsky, L.; Wijnands, R.; Maccarone, T.; et al. (Institute of Physics Publishing, 2018)
Transitional millisecond pulsars are accreting millisecond pulsars that switch between accreting X-ray binary and millisecond radio pulsar states. Only a handful of these objects have been identified so far. Terzan 5 CX1 is a variable hard-X-ray source in the globular cluster Terzan 5. In this paper, we identify a radio counterpart to CX1 in deep Very Large Array radio continuum data. Chandra observations over the last 14 years indicate that CX1 shows two brightness states: in 2003 and 2016 the source was the brightest X-ray source in the cluster (at L X ~ 1033 erg s-1), while in many intermediate observations, its luminosity was almost an order of magnitude lower. We analyze all available X-ray data of CX1, showing that the two states are consistent with the spectral and variability properties observed for the X-ray active and radio pulsar states of known transitional millisecond pulsars. Finally, we discuss the prospects for the detection of CX1 as a radio pulsar in existing timing data.